Factors influencing parents’ hesitancy to vaccinate their children aged 5–11 years old against COVID-19: results from a cross-sectional study in Malaysia - Marzo, Roy Rillera; Chakraborty, Ritankar; Soh, Shean Yih; Thew, Hui Zhu; Chong, Collins; Siau, Ching Sin; Abdul Wahab, Khairuddin Bin; Binti Ariffin, Indang Ariati; Chauhan, Shekhar; Brackstone, Ken; Padhi, Bijaya Kumar; Heidler, Petra (Frontiers in Public Health, 2023)
Introduction Vaccination programs have been rolled out across the globe to contain and mitigate the spread of the COVID-19 infection. Until recently, such programs were limited to adults and the older population, thereby limiting children from getting vaccinated. Recently, the Malaysian government rolled out vaccination for children aged 5–11 years. However, there are certain factors that might affect vaccination uptake among children. This study explores factors influencing parents’ hesitancy to vaccinate children in Malaysia. Method A nationwide online cross-sectional convenience sampling survey from April 21, 2022 to June 3, 2022 was conducted. The study used descriptive statistics to inform about vaccine hesitancy among parents. Cross-tabulation was performed to calculate the frequency and percentage of vaccine hesitancy, quality of life, e-health literacy, and the 5C psychological antecedents of vaccination among parents with children 5-11 years in Malaysia. Graphical methods were used to portray the levels of e-health literacy and levels of 5C psychological antecedents of vaccination. The study used both bi-variate and multivariate analysis to understand the relationship between vaccine hesitancy and the socio-demo-economic factors, quality of life, e-health literacy and 5C psychological antecedents. Results Of 382 participants, almost one-third (33%) of participants reported vaccine hesitancy for their children. For 5C’s psychological antecedents of vaccination, around one quarter (26.96%) reported disagreement for confidence in vaccination, almost half (52.36%) reported disagreement for vaccination complacency, three-fifths (60.99%) reported vaccination constraint, one quarter (25.92%) reported calculation antecedent, and almost one-third reported disagreement over collective responsibility antecedent (25.92%). Chi-square test revealed that gender, employment status, and parents’ COVID-19 vaccination status were significantly associated (p<0.05) with vaccine hesitancy among parents. Assessing the influence of transactional e-health literacy, only the communication component contained a significant association (p<0.05). Among the 5C psychological antecedents, confidence, calculation, and collective responsibility were significantly associated (p<0.05) with vaccine hesitancy. Parents with secondary [OR: 8.80; CI: 2.44−31.79, (p<0.05)], post-secondary [OR: 5.21; CI: 2.10-13.41, (p<0.05)], and tertiary education [OR: 6.77; CI: 2.25−20.35, (p<0.05)] had significantly higher likelihood of vaccine hesitancy than those with primary education. Conclusion Highly educated parents are more skeptical and are more likely to perceive the vaccine as unsafe and ineffective for their children. It is critical to disseminate the required information about the vaccine safety to the educated group.